2017
DOI: 10.1371/journal.pone.0183548
|View full text |Cite
|
Sign up to set email alerts
|

In silico analysis of protein toxin and bacteriocins from Lactobacillus paracasei SD1 genome and available online databases

Abstract: Lactobacillus paracasei SD1 is a potential probiotic strain due to its ability to survive several conditions in human dental cavities. To ascertain its safety for human use, we therefore performed a comprehensive bioinformatics analysis and characterization of the bacterial protein toxins produced by this strain. We report the complete genome of Lactobacillus paracasei SD1 and its comparison to other Lactobacillus genomes. Additionally, we identify and analyze its protein toxins and antimicrobial proteins usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 90 publications
1
20
0
Order By: Relevance
“…Similar to our study, it has been observed that bacteriocins encoded by Lactobacillus are species, strain, and origin dependent (59). The different classes of bacteriocins detected from L. paracasei 3E were similar to those observed with the probiotic strain L. paracasei SD1 (60). Expression of these bacteriocins may have led to L. paracasei 3E being one of the strongest inhibitors of M. haemolytica (ZOI, Ͼ22 mm).…”
Section: Discussionsupporting
confidence: 88%
“…Similar to our study, it has been observed that bacteriocins encoded by Lactobacillus are species, strain, and origin dependent (59). The different classes of bacteriocins detected from L. paracasei 3E were similar to those observed with the probiotic strain L. paracasei SD1 (60). Expression of these bacteriocins may have led to L. paracasei 3E being one of the strongest inhibitors of M. haemolytica (ZOI, Ͼ22 mm).…”
Section: Discussionsupporting
confidence: 88%
“…The procedure was highly selective for large DNA fragments while excluding smaller plasmid DNAs from the sequencing reaction. Often, the PacBio sequencing was regarded as the platform providing complete genomic information as both chromosome and large plasmids, usually with the size larger than 10 kb, were detected 7,8 . Thus, the presence of small plasmids and their associated risk were not determined.…”
Section: Resultsmentioning
confidence: 99%
“…To the best of our knowledge, despite suggestions on the issues that should be investigated for microbial safety assessment 6,17 , no clear procedural guideline have been provided. Despite several studies reported on microbial safety assessements 7,11,14,27 , no consensual procedure agreement can be observed. Therefore, we would like to propose the guideline for conducting the microbial safety evaluation using the whole-genome analysis as follow:…”
Section: Safety Conclusion Of L Plantarum Bcc9546mentioning
confidence: 87%
See 1 more Smart Citation
“…We found that eight Lactobacillus isolates could reduce C. albicans hyphae formation, and L. paracasei 28.4 showed the greatest amount of reduction. This fact could be due to the Lactobacillus production of antimicrobial molecules such as bacteriocins, since the reduction of the pH was not significant [46,47].…”
Section: Discussionmentioning
confidence: 99%